Farmer-preferred traits and variety choices for finger millet in Uganda - Hamba, S.; Kasule, F.; Mayanja, I.; Biruma, M.; Natabirwa, H.; Sanya, L.N.; Rubin, D.; Occelli, M.; Adikini, S. (Frontiers Media, 2024)
Finger millet is a climate-resilient crop providing food and nutrition security and income In Uganda. However, the current productivity of finger millet in farmers’ fields is low and among other factors, this is due to the poor adoption of improved varieties. With this study we aim to identify and profile varietal traits preferred by finger millet farmers and consumers in Uganda. We specifically focus on how these traits vary among women and men in the Ugandan finger millet value chain. We collect data using semi-structured questionnaires among 170 households growing millet in Bushenyi, Lira, and Nwoya districts, and we triangulate questionnaires replies with qualitative information from 11 focus group discussions and 3 key informant interviews. Using descriptive statistics and probit regression models, we find that the majority of the farmers (97%) prefer growing landrace varieties of finger millet compared to only 3% growing improved varieties. The most preferred varieties were Kaguma in Bushenyi, Ajuko Manyige in Nwoya, Kal Atar, and Okello Chiba in Lira. Farmers’ choice of variety depends on a combination of traits including agronomic, marketing, and consumption traits. Gender, marital status, education levels, and occupation are the major socio-demographic factors that influence specific preferences related to finger millet variety. This study lays a foundation for designing a gender-responsive finger millet product profile to guide the development and release of new varieties by the finger millet crop improvement program.